2022
DOI: 10.1039/d1py01711j
|View full text |Cite
|
Sign up to set email alerts
|

From poly(vinylimidazole) to cationic glycopolymers and glyco-particles: effective antibacterial agents with enhanced biocompatibility and selectivity

Abstract: Cationic glycopolymers have attracted great attention as a new type of antibacterial material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Through this combination, their cationic glycopolymers retained their antibacterial activity against Gram-positive S. aureus and Gram-negative E. coli , and now also allowed for detection and imaging of the bacteria through fluorescence being induced only upon clustering of the bacteria with the polymer. In a follow-up study, 139 the group also reported a new one-step reaction to produce mannose or glucose-containing N -alkyl imidazole-based block-copolymers, which were used to construct core or surface-functionalized glyconanoparticles from different solvents. By tuning selected structural parameters such as the molecular weight, they determined thresholds for maximization of antibacterial activity while reducing hemolytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Through this combination, their cationic glycopolymers retained their antibacterial activity against Gram-positive S. aureus and Gram-negative E. coli , and now also allowed for detection and imaging of the bacteria through fluorescence being induced only upon clustering of the bacteria with the polymer. In a follow-up study, 139 the group also reported a new one-step reaction to produce mannose or glucose-containing N -alkyl imidazole-based block-copolymers, which were used to construct core or surface-functionalized glyconanoparticles from different solvents. By tuning selected structural parameters such as the molecular weight, they determined thresholds for maximization of antibacterial activity while reducing hemolytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…It may be noted here that the charge density of quaternary ammonium polymers plays a vital role in antimicrobial properties. 19,20 The charge density is predominantly determined by the nature and concentration of the tertiary amine. The high charge density is also the source of the hemolytic and cytotoxic nature of these polymers.…”
Section: Introductionmentioning
confidence: 99%
“…19 The re-engineering process is generally achieved by constructing cationic antibacterial materials from these natural bactericides. [20][21][22] In comparison with AMPs, lysozyme is an ideal base material for composite bactericides as it possesses a better surface chemistry environment that can be further functionalized. [23][24][25] The anti-bacterial mechanism of lysozyme involves its ability to hydrolyse β-1,4-linked glycoside bonds of the peptidoglycan component of bacterial cell walls.…”
mentioning
confidence: 99%